STUDI KUALITAS AIR PAYAU UNTUK BUDIDAYA PERIKANAN DI KAWASAN PESISIR KECAMATAN LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - Putra, Reza Rammiko; Hermon, Dedi; Farida, Farida (Pendidikan Geografi, 2013)
This study aims is to obtain data and information and to discuss about brackish water quality which suitable for aquaculture in coastal area of Muara Air Jambu and Muara Gadang in District Linggo Sari Baganti covering physical conditions (temperature, brightness, and salinity) and chemical conditions (DO, pH, CO2, and NH3). This research is a descriptive study. Determination of sample points in the study done by using purposive sampling technique that is based on a unit area of Muara Air Jambu and coastal area Muara Gadang in District Linggo Sari Baganti. Each unit area represented one sample point brackish water, the amount of water sample point to be taken is 2 sample points on each unit. Based on field observations and laboratory analysis, the obtained results that the brackish water in the study area ofÂ  Muara Air Jambu Beach seen from the physical and chemical conditions are meet water quality standards for aquaculture according to Government Regulation No.. 20 in 1990, and categorized in the appropriate class, but there are some unfavorable factors such as salinity, pH, and DO. Brackish water in coastal research Muara Gadang Beach is seen from the physical and chemical conditions also have to meet water quality standards for aquaculture fisheries according to Government Regulation No.. 20 in 1990, and categorized in the appropriate class, but there are some unfavorable factors such as salinity, pH, and DO.